Health equity message framing: a Canadian regional health authority perspective. Issue 2 (4th March 2017) - Lammertsen, Ryan C.; Tong, Samantha; Nguyen, Amelie T.; Lee, Victoria
Abstract : Objective: How health equity is communicated plays an important role in how it is perceived, and to what degree it will inspire collective action. The goal of this mixed-methods study is to develop and test health equity messages to: (1) determine which messages resonate most amongst health care staff and leaders of the Fraser Health Authority (FH); (2) compare these results with that from the United States; and (3) contribute to health equity message framing in Canada.Methods: Twelve health equity statements and packages were developed and piloted between June and August 2012. Quantitative data were collected through a semi-structured survey with FH upper management ( n = 468) at a quarterly business meeting and focus groups; data were analysed using ANOVA and Tukey HSD statistical tests. Qualitative data were gathered through a series of 11 focus group discussions with health care staff ( n = 55) and analysed using NVIVO 10.Results: The diverse cultural values present within the FH region carried significantly more weight in message resonance than 'Canadian' values. Health equity statements with action-oriented solutions were favoured. Messages need to be clear, simple and concise, colloquial and cohesive. Relevant, broader and inclusive messages, with context, were preferred.Conclusion: This study highlights how health equity messages could be framed at FH and differences between Canadian and American messaging preferences. Our results present opportunities to improve future health equity messaging within the Canadian context so that we can engage a wide range of audiences on social change towards health equity.